Iowa RBA, April 21, 1997 - Hoskins, Nelson R.et al; Clark, Joeet al (1997)
Iowa RBA update for April 21, 1997. Highlights of the update include the appearance of a potential first state record of a White-winged Dove as well as sightings of Cinnamon Teals, a Red-throated Loon, a Pacific Loon, and a Glaucous Gull. Also of note were several returning birds, including Blue-gray Gnatcatcher, Yellow-headed Blackbird, Northern Parula, Broad-winged Hawk, and Osprey. Also included are handwritten notes for the next week's update with sightings of a Long-tailed Duck, Spotted Towhees, and Eurasian Tree Sparrows. Epson - sheet feed/flatbed